Hybrid-Type SELEX for the Selection of Artificial Nucleic Acid Aptamers Exhibiting Cell Internalization Activity - Hiro Uemachi; Yuuya Kasahara; Keisuke Tanaka; Takumi Okuda; Yoshihiro Yoneda; Satoshi Obika (MDPI AG, 2021)
Nucleic acid aptamers have attracted considerable attention as next-generation pharmaceutical agents and delivery vehicles for small molecule drugs and therapeutic oligonucleotides. Chemical modification is an effective approach for improving the functionality of aptamers. However, the process of selecting appropriately modified aptamers is laborious because of many possible modification patterns. Here, we describe a hybrid-type systematic evolution of ligands by exponential enrichment (SELEX) approach for the generation of the artificial nucleic acid aptamers effective against human TROP2, a cell surface protein identified by drug discovery as a promising target for cancer therapy. Capillary electrophoresis SELEX was used for the pre-screening of multiple modified nucleic acid libraries and enrichment of TROP2 binding aptamers in the first step, followed by functional screening using cell-SELEX in the second step for the generation of cell-internalizing aptamers. One representative aptamer, Tac-B1, had a nanomolar-level affinity to human TROP2 and exhibited elevated capacity for internalization by cells. Because of the growing interest in the application of aptamers for drug delivery, our hybrid selection approach has great potential for the generation of functional artificial nucleic acid aptamers with ideal modification patterns in vitro.